Excluded form citizenship with Pericle’s Law (Plut. Per. 37.3-4): Some reflexions about citizens, foreign people and slaves in Fifht Century BC Athens. (De Rebus Antiquis, 2021)
In the year 445, in the middle of Pentecontaetia, an extensive review of citizens was carried out as a result of a wheat donation by Psammetichus from Egypt and as a consequence of the recent Pericles citizenship law (451). In this citizen review it appears that many xenoi fraudulently enrolled in demes and phratries are driven out and sold as slaves. In these pages I explore the possibility, already pointed out by Patterson in 1981, of the fraudulent integration of many lower-class foreigners in the Athenian demos, among thetes, which contributed to increase exponentially -along with the general economic prosperity and the empire- the Athenian population of those years. This led to enabling forms of citizen control that seem to have fallen into disuse during the Peloponnesian War due to the human losses of those years. This occurs in a generalized environment in which marginal / marginalized sectors of the population such as the allied xenoi, metics, atimoi and slaves are similarly perceived in the shared imaginary constructs of Athens.
Keywords: xenoi; diapsephismos; graphe xenias; Pericles law; citizenship; lower classes